Relation of soluble RANKL and osteoprotegerin levels in blood and gingival crevicular fluid to the degree of root resorption after orthodontic tooth movement. - Tyrovola, Joanna B; Perrea, Despoina; Halazonetis, Dimitrios J; Dontas, Ismene; Vlachos, Ioannis S; Makou, Margarita (J Oral Sci, 2010)
The aim of the present study was the determination of the levels of osteoprotegerin and soluble RANKL in blood serum and in gingival crevicular fluid relative to the degree of orthodontic root resorption in a rat model. Blood samples and gingival crevicular fluid were collected from fourteen 6-month-old male Wistar rats weighing 350-500 g. A 25-g closed orthodontic coil spring was inserted between each upper right first molar and the upper incisors. After 21 days of loading, both upper first molars (treated and control) were extracted and studied under microcomputed tomography scanning. Statistical analysis demonstrated a positive linear correlation between the initial concentration of RANKL in blood serum and the degree of root resorption. The ratio of the initial concentrations of osteoprotegerin to RANKL in blood serum proved to be an independent prognostic factor of the degree of root resorption. The initial concentration of RANKL in gingival crevicular fluid showed a negative correlation to the initial concentration of RANKL in blood serum and for a finite range of initial concentrations of osteoprotegerin in gingival crevicular fluid, the dental root seemed protected against extreme external root resorption. Finally, the concentration of osteoprotegerin in blood serum decreased significantly in cases of severe root resorption.
Keywords: Animals; Disease Models, Animal; Gingival Crevicular Fluid; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Incisor; Male; Molar; Orthodontic Wires; Osteoprotegerin; RANK Ligand; Rats; Rats, Wistar; Root Resorption; Stress, Mechanical; Tooth Movement Techniques; Tooth Root; X-Ray Microtomography